1996
DOI: 10.1063/1.115912
|View full text |Cite
|
Sign up to set email alerts
|

Nanoparticle deposition in hydrogenated amorphous silicon films during rf plasma deposition

Abstract: Particles of 2–14 nm diameter, representing 10−4–10−3 of the film volume, are observed by scanning tunneling microscopy (STM) in thin films of hydrogenated amorphous silicon (a-Si:H) grown by rf-plasma-enhanced deposition using optimized conditions. The particles are produced in the discharge and incorporated in the film during growth, in contradiction to expected particle trapping by discharge sheath fields. The interfaces between the nanoparticles and the homogeneous film can produce low-density regions that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
33
0

Year Published

1997
1997
2008
2008

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 66 publications
(33 citation statements)
references
References 13 publications
0
33
0
Order By: Relevance
“…These images are excluded from the analysis in this paper, but are the subject of a previous publication. 21 The undoped a-Si:H typically has a low-field resistivity Ͼ10 9 ⍀ cm. A calculation of spreading resistance for current injected from a subnanometer point contact using this number suggests that it would be impossible to conduct these tunneling currents through the films.…”
Section: Data Collectionmentioning
confidence: 99%
See 2 more Smart Citations
“…These images are excluded from the analysis in this paper, but are the subject of a previous publication. 21 The undoped a-Si:H typically has a low-field resistivity Ͼ10 9 ⍀ cm. A calculation of spreading resistance for current injected from a subnanometer point contact using this number suggests that it would be impossible to conduct these tunneling currents through the films.…”
Section: Data Collectionmentioning
confidence: 99%
“…20 Pockets of clustered H atoms are reported by NMR measurements. 21 These types of features make the density of a-Si:H ϳ5% lower than crystalline silicon ͑c-Si͒. Our previous scanning tunneling microscope ͑STM͒ studies of a-Si:H films revealed a surprisingly wide variety of topographic features, including the incorporation of nanoparticles in the films from the plasma.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…7 These cause nonuniformity in the deposited films, and in extreme cases lead to unacceptable contamination rendering the material unusable for electronic applications. 8 This has led to a number of publications focused on understanding the formation, dynamics, and consequences of these terrestrial dusty plasmas, with regard to silicon-based PECVD dust. 9 However, the development of amorphous hydrogenated carbon ͑a-C:H͒ 10 devices formed from a methane precursor, for example, is still very much in its infancy, and little attention has so far been paid to the nature of carbonaceous dusty plasmas.…”
mentioning
confidence: 99%
“…Even when they are so small that they are not able to cause any damage during the plasma processing of micro components they may be embedded into the film matrix changing the film properties and forming defects and voids at the interface with the surrounding film [34]. Sometimes the incorporation of the nanoparticles is wanted in plasma processing of the film because this is the only way to achieve desirable properties as for example in the case of photoluminescent thin films deposited in silane plasma with embedded crystalline clusters with sizes of 1 to 5 nm [35].…”
Section: Introductionmentioning
confidence: 99%